Ecotoxicological profile of a high prevalence marine disease area in Florida's Gulf coast - Manes Costanza; Herren Richard; Kozuch Marianne; Cooper Evan; Lilyestrom Margaret; Evans Daniel; Godfrey David; Duffy David; Capua Ilaria; Carthy Raymond (Marine Pollution Bulletin, 2026)

Cross life cycle opportunities for increasing the post-consumer recycled content of aluminum automotive body sheet in the United States - Alissa Tsai; Yongxian Zhu; Mohammadreza Heidari; Daniel R. Cooper (Journal of Industrial Ecology, 2026)
Increasing the post-consumer recycled content (PCRC) of aluminum automotive body sheet (ABS) is a promising pathway to reduce greenhouse gas (GHG) emissions from ABS production. However, progress is constrained by the limited end-of-life vehicle (ELV) ABS scrap available and the compositional mismatches between contaminated scrap streams and alloy specifications. This study identifies cross ABS life cycle strategies that sheet mills, automotive OEMs, and recyclers can implement and quantifies their effects using a composition-specific dynamic material flow analysis to model sheet demand and scrap availability coupled with a linear optimization framework that determines annual PCRC potential under product-demand, scrap-supply, and alloy-composition constraints. A supply chain emissions model links PCRC gains to GHG reductions. By 2050, ABS scrap from U.S. ELVs could supply up to 33% of the ABS ingot demand needed to meet U.S. requirements for ABS components, yet PCRC remains negligible under business-as-usual (BAU) strategies due to compositional incompatibilities. Effective strategies to increase the PCRC include: (1) sheet mills developing high-residual-content (HRC) “recycle-friendly” alloys; (2) OEMs shifting 5xxx-series component designs to 6xxx alloys; and (3) recyclers either extracting sheet-rich sub-assemblies before shredding or adopting advanced sorting technologies to separate shredded ELV aluminum scrap by alloy series. Achieving a PCRC that approaches the physical maximum (33%) occurs only when multiple stakeholders act to implement complementary strategies. The combination of ELV scrap sorting by alloy series and deployment of HRC alloys is particularly effective. Together, these measures could raise PCRC to 28% by 2050, increase total scrap content (including production scrap) to 76%, and cut annual ABS component supply chain emissions by up to 42%.

Identifying potential invasion hotspots for non-native fluvial fishes throughout the conterminous United States - Hao Yu; Arthur R. Cooper; Jared A. Ross; Wesley M. Daniel; Jack E. Taylor; Alina Sargsyan; Dana M. Infante (Biological Invasions, 2026)
Identifying habitats that non-native fluvial fishes are likely to invade provides information for proactive management, conservation planning, and understanding the ecology of biological invasions. We identified streams in the conterminous United States with high invasion risk from 20 non-native fluvial fish species. Specifically, we (1) developed habitat suitability models for each species using nine natural and six anthropogenic predictors within nine large ecoregions, identifying the potential invasion hotspots; (2) evaluated the relative importance of natural and anthropogenic predictors for each species; and (3) assessed potential invasion risk to protected stream habitats. Predicted invasion hotspots included much of Florida, coastal regions of Texas and Louisiana, and areas surrounding major metropolitan centers such as Chicago, New York, and Phoenix. Model predictions indicate that goldfish ( Carassius auratus ), pirapitinga ( Piaractus brachypomus ), and pond loach ( Misgurnus anguillicaudatus ) could occupy extensive suitable habitats across the conterminous United States. The most influential natural predictor across species was network catchment area (a surrogate for stream size), while the most influential anthropogenic predictor was human population density. Goldfish were predicted to be present in protected areas across all nine ecoregions, highlighting their high invasion potential. Collectively, our results provide critical information on regions vulnerable to invasion and the species most likely to become established and identify areas at risk of invasion within protected landscapes.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Integration of ploidy, Orc1/Cdc6 homolog function, and lysine acetylation with phosphate limitation and UV stress responses of Haloferax volcanii - Daniel Gal; Colton Smith; Kelsey Cooper; Ricardo L. Couto-Rodríguez; Julie A. Maupin-Furlow (Extremophiles, 2026)

Decoupled Climatic Drivers of Tree and Ground‐Layer Carbon Uptake in Mountain Ecosystems Around the World - Max Mallen‐Cooper; Maja K. Sundqvist; David A. Wardle; Radim Šarlej; Rose E. Brinkhoff; Aimée T. Classen; Eliška Kuťáková; Daniel B. Metcalfe; M. Noelia Barrios‐Garcia; Julie R. Deslippe; Kobayashi Makoto; Jane Mallen‐Cooper; et al. (Global Change Biology, 2026)
One of the key ecological processes affected by climate change is plant carbon uptake. However, there is substantial uncertainty about how plant carbon uptake will respond to warming in mountain ecosystems, which are known for sharp temperature gradients and abrupt shifts in vegetation structure. Specifically, we lack an understanding of whether these response trajectories over time will be linear or non‐linear, and how they might vary among mountain ecosystems globally. Here, we measured ecosystem Gross Primary Productivity (GPP) along forest‐tundra elevational gradients in the mountain regions of five countries (Argentina, Australia, France, Sweden, USA) to infer future trajectories of carbon uptake, and whether any non‐linear changes might occur. We also examined the role of microclimate in driving GPP responses. We found that whole‐ecosystem GPP increased with increasing macroclimatic temperature (decreasing elevation), but this response was dominated by a sharp non‐linear increase at the transition from tundra to forest (i.e., the treeline). In contrast, ground‐layer GPP was largely independent of macroclimate, but often responded strongly, and linearly, to microclimate (growing degree days > 5°C, mean growing season temperature). This pattern reflected a frequent decoupling of microclimate from the expected temperature‐elevation relationship, likely driven by such processes as cold‐air drainage, limited near‐surface air mixing, and shading by trees. The contrasting responses of GPP among global temperature gradients indicates strong context dependence at both local and continental scales, although in a few cases, biomass and leaf nitrogen were important moderators. These findings suggest that future shifts in carbon uptake in mountains will be mainly controlled by tree range expansion. Our results highlight the need to consider species responses on different spatial scales, and to increase representation of undersampled regions to capture the full breadth of ecological responses to climate change.

Mapping the global flow of fiber-reinforced polymer composites and supply chain energy requirements - Zhuoer Li; Mihaela Banu; Daniel R. Cooper (Resources, Conservation and Recycling, 2026)

Drained Agricultural Peatlands as Persistent Carbon Sources: Implications for Carbon and Water Use Intensity in Food Production - Brenda D'Acunha; Chris D. Evans; Alanna Bodo; Hollie Cooper; Dafydd Egryn Crabtree; Alexander Cumming; Jennifer M. Rhymes; Daniel Rylett; Rebekka R. E. Artz; Ross Morrison (Global Change Biology, 2026)
Peatlands have the capacity to sequester large quantities of carbon and can therefore play an important role in climate change mitigation. However, anthropogenic activities alter their hydrological regimes, converting them from net CO 2 sinks into net sources. In England and elsewhere, lowland peatlands have been heavily drained and modified for agricultural land use, resulting in some of the most productive farmland in the UK. Estimates of CO 2 emissions and water use from the area are scarce, but these data are required to understand the consequences of maintaining agricultural output whilst simultaneously reducing GHG emissions. In this paper, we compiled a uniquely comprehensive dataset of CO 2 and H 2 O flux measurements from flux towers on cropped lowland peat, and coupled this with crop calorific values to estimate carbon and water use intensities of food production on peat. Our results showed that croplands on peat emitted 23.1 ± 10.4 ton CO 2 ha −1 y −1 (mean ± SD). Sites with peat depth > 40 cm emitted 25.1 ± 9.2 ton CO 2 ha −1 , while wasted peat sites emitted 11.8 ± 4.8 ton CO 2 ha −1 . Effective water table depth and organic carbon content were the main drivers of variation in annual net ecosystem production and ecosystem respiration across sites; crop type partly followed these gradients, so may not be a direct driver of variations in emissions. ET was less variable across site‐years and depended on the phenology of crop production. When considering CO 2 emissions and water use per calorie produced, lettuce and celery rotations were the most C and water use intensive crops, with values an order of magnitude larger than cereal crops. Overall, this paper highlights the scale of CO 2 emissions from managed peatlands and the importance of balancing GHG emissions and water use with ongoing food production from these economically important areas.

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Circular economy pathways for decarbonizing aluminum and steel automotive body sheet components in the United States - Mohammadreza Heidari; Yongxian Zhu; Alissa Tsai; Gregory A. Keoleian; Hyung Chul Kim; Robert De Kleine; Jarod Kelly; Siddharth Shukla; Daniel R. Cooper (Resources, Conservation and Recycling, 2026)

Decarbonizing the U.S. aluminum ecosystem using a dynamic material flow simulation framework - Sidi Deng; Yongxian Zhu; Alissa Tsai; Daniel R. Cooper (Journal of Cleaner Production, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Intelligent data collection for reducing network structure uncertainty in material flow analysis using Bayesian optimal experimental design - Jiankan Liao; Xun Huan; Daniel Cooper (Journal of Industrial Ecology, 2025)
Material flow analyses (MFAs) are powerful tools for highlighting resource efficiency opportunities in supply chains. MFAs are often represented as directed graphs, with nodes denoting processes and edges representing mass flows. However, network structure uncertainty—uncertainty in the presence or absence of flows between nodes—is common and can compromise flow predictions. While collection of more MFA data can reduce network structure uncertainty, an intelligent data acquisition strategy is crucial to optimize the resources (person‐hours and money spent on collecting and purchasing data) invested in constructing an MFA. In this study, we apply Bayesian optimal experimental design, based on the Kullback–Leibler divergence, to efficiently target high‐utility MFA data—data that minimizes network structure uncertainty. We introduce a new method with reduced bias for estimating expected utility, demonstrating its superior accuracy over traditional approaches. We illustrate these advances with a case study on the US steel sector MFA, where the expected utility of collecting specific single pieces of steel mass flow data aligns with the actual reduction in network structure uncertainty achieved by collecting said data from the United States Geological Survey and the World Steel Association. The results highlight that the optimal MFA data to collect depends on the total amount of data being gathered, making it sensitive to the scale of the data collection effort. Overall, our methods support intelligent data acquisition strategies, accelerating uncertainty reduction in MFAs and enhancing their utility for impact quantification and informed decision‐making.

Soil porosity in integrated and non-integrated grazing systems in a Brazilian Ferralsol assessed by 3D X-ray computed tomography - Gustavo Pereira Valani; Aline Fachin Martíni; Cássia Bezerra Machado; Daniel Amancio Duarte; Marcio Fernando Paixão de Brito; José Ricardo Macedo Pezzopane; Alberto Carlos de Campos Bernardi; Antonio Celso Dantas Antonino; Richard John Heck; Daniel Giménez; Miguel Cooper (Computers and Electronics in Agriculture, 2025)

Bayesian model selection for network discrimination and risk‐informed decision‐making in material flow analysis - Jiankan Liao; Sidi Deng; Xun Huan; Daniel Cooper (Journal of Industrial Ecology, 2025)
Material flow analyses (MFAs) provide insight into supply chain‐level opportunities for resource efficiency. MFAs can be represented as networks with nodes that represent materials, processes, sectors, or locations. MFA network structure uncertainty (i.e., the existence or absence of flows between nodes) is pervasive and can undermine the reliability of the flow predictions. This article investigates MFA network structure uncertainty by proposing candidate node‐and‐flow structures and using Bayesian model selection to identify the most suitable structures and Bayesian model averaging to quantify the parametric mass flow uncertainty. The results of this holistic approach to MFA uncertainty are used in conjunction with the input‐output (I/O) method to make risk‐informed resource efficiency recommendations. These techniques are demonstrated using a case study on the US steel sector where 16 candidate structures are considered. The model selection highlights two networks as most probable based on data collected from the United States Geological Survey and the World Steel Association. Using the I/O method, we then show that the construction sector accounts for the greatest mean share of domestic US steel industry emissions while the automotive and steel products sectors have the highest mean emissions per unit of steel used in the end‐use sectors. The uncertainty in the results is used to analyze which end‐use sector should be the focus of demand reduction efforts under different appetites for risk. This article's methods generate holistic and transparent MFA uncertainty that accounts for structural uncertainty, enabling decisions whose outcomes are more robust to the uncertainty.

Coexistence, Extinction and Survival—The Evolutionary History of Bison Species in Western Eurasia - Bastien Llamas; Ayla L. van Loenen; Kieren J. Mitchell; Emilia Hofman‐Kamińska; Hervé Bocherens; Holly Heiniger; Martina Pacher; Daniel Makowiecki; Giedrė Piličiauskienė; Dorothée G. Drucker; David Brown; Zoe A. Thomas; et al. (Global Change Biology, 2025)
European bison ( Bison bonasus ) are one of the few European megafaunal species to survive the Late Pleistocene mass megafaunal extinction. Current conservation management efforts have proceeded in the absence of information about their evolutionary history, which has been obscured by recent severe population bottlenecks. We characterized mitochondrial genomes from 135 ancient bison samples spanning > 50,000 years (> 50 ka) across the Eurasian continent and detected three distinct phylogenetic groups: two distinct clades of European bison and the extinct steppe bison ( Bison priscus ). The geographical distributions and dietary/ecological signatures of the three groups overlapped during the Late Pleistocene climate cycles and tracked environmental changes including vegetation cover and human impacts. The abundance of European bison specimens responded negatively to the extent of forest cover, including Holocene cycles of abrupt atmospheric‐ocean circulation changes originating in the North Atlantic. European bison remain preferentially adapted to an open environment, but with today's anthropogenic landscapes, are now largely restricted to forest habitats with negative implications under scenarios of future environmental change.

Irrigation reshapes weathering and pedogenesis in calcareous soils of tropical dryland (NE Brazil) - Lucas Resmini Sartor; Francisco Ruiz; Priscilla Alves da Costa; Daniel Pontes de Oliveira; Ricardo Espíndola Romero; Valdomiro Severino de Souza Júnior; Marcelo Metri Corrêa; Miguel Cooper; Tiago Osório Ferreira (CATENA, 2025)

Towards more circular building services: A social footprint of the sectors manufacturing and remanufacturing chillers for the European market - Sébastien Loreau; André Stephan; Daniel Cooper (The International Journal of Life Cycle Assessment, 2025)

Analysis of scrap flows from recycling aluminum-intensive vehicles in the United States: Insights from a case study on the F-150 - Yongxian Zhu; Omer Khan; Mohammadreza Heidari; Alissa Tsai; Laurent Chappuis; Constantin Chiriac; Daniel Freiberg; Aya Hamid; Hyung Chul Kim; Robert De Kleine; Arjun Sundararajan; Daniel R. Cooper (Resources, Conservation and Recycling, 2025)

Using cationic liposomes as carriers for long dsRNA to trigger an antiviral response in rainbow trout cell lines - Shayne J. Oberhoffner; Dominique E. Daniels; Erin Cooper; Aizah Ijaz; Starla A. Richardson; Stephanie J. DeWitte-Orr (In Vitro Cellular & Developmental Biology - Animal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Associations between social behaviour and proinflammatory immune activation are modulated by age in a free-ranging primate population - Eve B. Cooper; Connor Whalen; Nina Beeby; Josué E. Negron-Del Valle; Daniel Phillips; Noah Snyder-Mackler; Lauren J.N. Brent; James P. Higham (Animal Behaviour, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Human activity selectively affects a dynamic defensive mutualism - Bailey Franco; Cooper Kinne; Savannah Licciardello; Hali Muir; Holland J. Smith; Sean O'Fallon; Daniel T. Blumstein (Animal Behaviour, 2024)

Clay mineral composition drives soil structure behavior and the associated physical properties in Brazilian Oxisols - Thaís Nascimento Pessoa; Renata Cristina Bovi; Márcio Renato Nunes; Miguel Cooper; Daniel Uteau; Stephan Peth; Paulo Leonel Libardi (Geoderma Regional, 2024)

Lithotype composition and micro-topographic features: Drivers of soil variability on semiarid limestone plateaus - Daniel Pontes de Oliveira; Renata Cristina Bovi; Yuri Fernando Parra Castilho; Valdomiro Severino de Souza Júnior; Miguel Cooper; Hermano Melo Queiroz; Marcelo Metri Corrêa; Ricardo Espíndola Romero; Tiago Osório Ferreira (Geoderma Regional, 2024)

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

Cross-continental evaluation of landscape-scale drivers and their impacts to fluvial fishes: Understanding frequency and severity to improve fish conservation in Europe and the United States - Maria M. Üblacker; Dana M. Infante; Arthur R. Cooper; Wesley M. Daniel; Stefan Schmutz; Rafaela Schinegger (Science of The Total Environment, 2023)

Assessing the sustainability of laser powder bed fusion and traditional manufacturing processes using a parametric environmental impact model - Jiankan Liao; Robert De Kleine; Hyung Chul Kim; George Luckey; Joy Forsmark; Ellen C. Lee; Daniel R. Cooper (Resources, Conservation and Recycling, 2023)

An adaptable integrated modelling platform to support rapidly evolving agricultural and environmental policy - Paula A. Harrison; Kate Beauchamp; Joe Cooper; Ian Dickie; Alice Fitch; Richard Gooday; Michael Hollaway; Ian P. Holman; Merryn Hunt; Laurence Jones; Thomas Mondain-Monval; Daniel Sandars; et al. (Environmental Modelling & Software, 2023)

Immune cell composition varies by age, sex and exposure to social adversity in free-ranging Rhesus Macaques - Mitchell R. Sanchez Rosado; Nicole Marzan-Rivera; Marina M. Watowich; Andrea D. Negron-Del Valle; Petraleigh Pantoja; Melissa A. Pavez-Fox; Erin R. Siracusa; Eve B. Cooper; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Melween I. Martinez; et al. (GeroScience, 2023)

Expert elicitation and data noise learning for material flow analysis using Bayesian inference - Jiayuan Dong; Jiankan Liao; Xun Huan; Daniel Cooper (Journal of Industrial Ecology, 2023)
Bayesian inference allows the transparent communication and systematic updating of model uncertainty as new data become available. When applied to material flow analysis (MFA), however, Bayesian inference is undermined by the difficulty of defining proper priors for the MFA parameters and quantifying the noise in the collected data. We start to address these issues by first deriving and implementing an expert elicitation procedure suitable for generating MFA parameter priors. Second, we propose to learn the data noise concurrent with the parametric uncertainty. These methods are demonstrated using a case study on the 2012 US steel flow. Eight experts are interviewed to elicit distributions on steel flow uncertainty from raw materials to intermediate goods. The experts' distributions are combined and weighted according to the expertise demonstrated in response to seeding questions. These aggregated distributions form our model parameters' informative priors. Sensible, weakly informative priors are adopted for learning the data noise. Bayesian inference is then performed to update the parametric and data noise uncertainty given MFA data collected from the United States Geological Survey and the World Steel Association. The results show a reduction in MFA parametric uncertainty when incorporating the collected data. Only a modest reduction in data noise uncertainty was observed using 2012 data; however, greater reductions were achieved when using data from multiple years in the inference. These methods generate transparent MFA and data noise uncertainties learned from data rather than pre‐assumed data noise levels, providing a more robust basis for decision‐making that affects the system.

Evaluating potential changes to the US Chukchi Sea bottom trawl survey design via simulation testing - Zack S. Oyafuso; Lewis A. K. Barnett; Margaret C. Siple; Daniel W. Cooper; Stan Kotwicki (Frontiers in Marine Science, 2023)
The US Chukchi Sea consists of the waters off the northwest of Alaska and is a naturally dynamic ice-driven ecosystem. The impacts from climate change are affecting the Arctic marine ecosystem as well as the coastal communities that rely on healthy marine ecosystems. In anticipation of increased ecosystem monitoring in the area, there is an opportunity to evaluate improved sampling designs for future ecological monitoring of the Chukchi Sea, an area that is sampled less comprehensively compared to other regions in Alaska. This analysis focused on standardized NOAA-NMFS-AFSC bottom trawl surveys (otter and beam trawls) and three types of survey designs: simple random, stratified random, and systematic. First, spatiotemporal distributions for 18 representative demersal fish and invertebrate taxa were fitted using standardized catch and effort data. We then simulated spatiotemporal taxon densities to replicate the three survey design types to evaluate design-based estimates of abundance and precision across a range of sampling effort. Modest increases in precision were gained from stratifying the design when compared to a simple random design with either similar or lower uncertainty and bias of the precision estimates. There were often strong tradeoffs between the precision and bias of the systematic estimates of abundance (and associated variance) across species and gear type. The stratified random design provided the most consistent, reliable, and precise estimates of abundance indices and is likely to be the most robust to changes in the survey design. This analysis provides a template for changing bottom trawl survey designs in the Chukchi Sea and potentially other survey regions in Alaska going forward and will be important when integrating new survey objectives that are more ecosystem-focused.

Interplay between transcriptional regulators and VapBC toxin–antitoxin loci during thermal stress response in extremely thermoacidophilic archaea - Charlotte R. Cooper; April M. Lewis; Jaspreet S. Notey; Arpan Mukherjee; Daniel J. Willard; Paul H. Blum; Robert M. Kelly (Environmental Microbiology, 2023)
Thermoacidophilic archaea lack sigma factors and the large inventory of heat shock proteins (HSPs) widespread in bacterial genomes, suggesting other strategies for handling thermal stress are involved. Heat shock transcriptomes for the thermoacidophilic archaeon Saccharolobus ( f. Sulfolobus ) solfataricus 98/2 revealed genes that were highly responsive to thermal stress, including transcriptional regulators YtrA Ss (Ssol_2420) and FadR Ss (Ssol_0314), as well as type II toxin–antitoxin (TA) loci VapBC6 (Ssol_2337, Ssol_2338) and VapBC22 (Ssol_0819, Ssol_0818). The role, if any, of type II TA loci during stress response in microorganisms, such as Escherichia coli , is controversial. But, when genes encoding YtrA Ss , FadR Ss , VapC22, VapB6, and VapC6 were systematically mutated in Sa. solfataricus 98/2, significant up‐regulation of the other genes within this set was observed, implicating an interconnected regulatory network during thermal stress response. VapBC6 and VapBC22 have close homologues in other Sulfolobales, as well as in other archaea (e.g. Pyrococcus furiosus and Archaeoglobus fulgidus ), and their corresponding genes were also heat shock responsive. The interplay between VapBC TA loci and heat shock regulators in Sa solfataricus 98/2 not only indicates a cellular mechanism for heat shock response that differs from bacteria but one that could have common features within the thermophilic archaea.

Pacific cod or tikhookeanskaya treska (Gadus macrocephalus) in the Chukchi Sea during recent warm years: Distribution by life stage and age-0 diet and condition - Daniel W. Cooper; Kristin Cieciel; Louise Copeman; Pavel O. Emelin; Elizabeth Logerwell; Nissa Ferm; Jesse Lamb; Robert Levine; Kelia Axler; Rebecca A. Woodgate; Lyle Britt; Robert Lauth; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

A parametric life cycle assessment model for ductile cast iron components - Yongxian Zhu; Gregory A. Keoleian; Daniel R. Cooper (Resources, Conservation and Recycling, 2023)

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

Evidence of resident coastal population(s) of false killer whales (Pseudorca crassidens) in northern Australian waters - Carol Palmer; Karen K. Martien; Holly Raudino; Kelly M. Robertson; Alan Withers; Emma Withers; Robert Risk; Dylan Cooper; Ellen D’Cruz; Edmund Jungine; Daniel Barrow; Nick Cuff; et al. (Frontiers in Marine Science, 2023)
To help evaluate the distribution, residency, population size and structuring (and hence conservation status) of the poorly known false killer whale Pseudorca crassidens in northern Australian waters, we undertook studies of sightings, movement patterns based on satellite telemetry, and genetics. Sighting data indicates that false killer whales are regular, year-round inhabitants of coastal areas of northern Australia. Satellite-tagged animals spent extended periods of time in shallow coastal waters, with no tagged animals leaving the continental shelf. The lack of spatial overlap in the areas visited by individuals tagged in the Arafura/Timor Seas compared to those tagged in the Gulf of Carpentaria suggests that there may be more than one population in northern Australia coastal waters. All 14 genetic samples collected across 1600 km of coastline possessed the same newly identified mitochondrial control region haplotype, designated haplotype 45. Notably, haplotype 45 is distinct from all previously published false killer whale haplotypes globally and is most similar to the two haplotypes that typify the endangered main Hawaiian Islands insular false killer whale population. Based on these results and evidence from recent movement records of those tagged, false killer whales in northern Australia are apparently demographically independent from the offshore population(s). Further assessment of the population conservation status is now required.

Microbial communities and processes in biofilters for post-treatment of ozonated wastewater treatment plant effluent - Daniel Sauter; Andrea Steuer; Kenneth Wasmund; Bela Hausmann; Ulrich Szewzyk; Alexander Sperlich; Regina Gnirss; Myriel Cooper; Thomas Wintgens (Science of The Total Environment, 2023)

In-situ comparison between the energy performance of an in-slab gas heating system and a split system air conditioning in classrooms - Georgios Kokogiannakis; Daniel Daly; Clayton McDowell; James Roth; Michael Tibbs; Paul Cooper (Energy and Buildings, 2023)

The mitigating effect of masks on the spread of Covid-19 - Daniel Cooper; Vaishali Garga; María José Luengo-Prado; Jenny Tang (Economics & Human Biology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

A landscape approach for identifying potential reestablishment sites for extirpated stream fishes: an example with Arctic grayling (Thymallus arcticus) in Michigan - Ralph W. Tingley; Dana M. Infante; Emily M. Dean; Douglas W. Schemske; Arthur R. Cooper; Jared A. Ross; Wesley Daniel (Hydrobiologia, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Variables Influencing Differences in Sequence Conservation in the Fission Yeast Schizosaccharomyces pombe - Simon Emanuel Harnqvist; Cooper Alastair Grace; Daniel Charlton Jeffares (Journal of Molecular Evolution, 2021)
Which variables determine the constraints on gene sequence evolution is one of the most central questions in molecular evolution. In the fission yeast Schizosaccharomyces pombe , an important model organism, the variables influencing the rate of sequence evolution have yet to be determined. Previous studies in other single celled organisms have generally found gene expression levels to be most significant, with numerous other variables such as gene length and functional importance identified as having a smaller impact. Using publicly available data, we used partial least squares regression, principal components regression, and partial correlations to determine the variables most strongly associated with sequence evolution constraints. We identify centrality in the protein–protein interactions network, amino acid composition, and cellular location as the most important determinants of sequence conservation. However, each factor only explains a small amount of variance, and there are numerous variables having a significant or heterogeneous influence. Our models explain more than half of the variance in dN, raising the possibility that future refined models could quantify the role of stochastics in evolutionary rate variation.

Tolerance and avoidance of urban cover in a southern California suburban raptor community over five decades - Daniel S. Cooper; Pamela J. Yeh; Daniel T. Blumstein (Urban Ecosystems, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Effects of urbanization on population genetic structure of western gray squirrels - Christopher DeMarco; Daniel S. Cooper; Elizabeth Torres; Alan Muchlinski; Andres Aguilar (Conservation Genetics, 2021)

The potential for material circularity and independence in the U.S. steel sector - Daniel R. Cooper; Nicole A. Ryan; Kyle Syndergaard; Yongxian Zhu (Journal of Industrial Ecology, 2020)
Achieving a U.S. circular economy would reduce environmental impacts and increase material independence. This article calculates maximum recycled contents (RCs) and recycling rates (RRs) in an independent U.S. steel sector, and estimates the potential to displace current imports with recycled scrap that is currently destined for landfill, hibernating stocks, or export (LHSE). A U.S. dynamic material flow analysis (1880–2100) is conducted to estimate annual steel consumption and scrap generation. The results are coupled with a linear optimization model that minimizes primary steel demand while satisfying the volumetric and compositional demands of new consumption. The compositional analysis examines only copper content because it is of greatest concern to recyclers. The best estimate is that the maximum independent RR is already constrained by copper contamination. Without interventions, this maximum RR will gradually decline throughout the century. The annual consumption to scrap availability ratio (C2SR) will decrease from around 1.4 today. Concurrently, the maximum RC rises but then plateaus below 75% as the RR falls. This highlights a conflict in the conditions for a circular economy: a C2SR approaching unity is a necessary condition for a high RC but leads to fewer opportunities for scrap contaminant dilution, which decreases the RR. Improved product design for recycling and deployment of scrap refining technologies will be needed to reach higher RCs. In 2017, the mass of U.S. scrap destined for LHSE exceeded direct steel imports. Domestic recycling of scrap exports alone could have displaced 36% of direct steel imports, reducing the U.S. deficit by $5.5 billion.

Temperature–Induced Hatch Failure and Nauplii Malformation in Antarctic Krill - Frances A. Perry; So Kawaguchi; Angus Atkinson; Sévrine F. Sailley; Geraint A. Tarling; Daniel J. Mayor; Cathy H. Lucas; R. King; A. Cooper (Frontiers in Marine Science, 2020)

From Vagrant to Resident: occurrence, residency and births of leopard seals ( Hydrurga leptonyx ) in New Zealand waters - Krista Hupman; Ingrid N. Visser; Jim Fyfe; Martin Cawthorn; Giverny Forbes; Alexander A. Grabham; Rick Bout; Brittany Mathias; Ella Benninghaus; Kimberly Matucci; Tracy Cooper; London Fletcher; et al. (New Zealand Journal of Marine and Freshwater Research, 2020)
In contrast to previous reports that leopard seals ( Hydrurga leptonyx ) are rare vagrants to New Zealand, we show that this species is a regular member of the marine fauna of this region. We present a first analysis from the New Zealand Leopard Seal Database – an extensive collation of 2,711 records of leopard seals within New Zealand between 1200 and 2018. Of these records, 51.2% ( n = 1,408) were photographic. Leopard seal sightings have increased over time and been reported in all seasons and regions of New Zealand. Sightings are predominantly of adult individuals of good or excellent body condition, which differs to previous hypotheses suggesting that leopard seals visiting New Zealand shores are primarily juvenile animals in poor health condition. A total of 176 unique individuals have been identified in the New Zealand Leopard Seal Catalogue between 2014 and 2018 and preliminary results indicate that numbers per annum have continued to increase over time. Three leopard seal births and a number of juvenile animals (34% of the NZ records) have been documented. Considering the information presented here and the current definitions in the New Zealand Threat Classification System, the threat status of leopard seals within New Zealand waters should be reclassified from Vagrant to Resident.

Environmentally driven forecasts of northern rock sole ( Lepidopsetta polyxystra ) recruitment in the eastern Bering Sea - Daniel Cooper; Lauren A. Rogers; Thomas Wilderbuer (Fisheries Oceanography, 2020)
Northern rock sole recruitment in the eastern Bering Sea has been hypothesized to (a) depend on wind‐driven surface currents linking spawning and nursery areas, (b) be density‐dependent, and (c) be negatively impacted by cold bottom temperatures over a large nursery area during the first summer of life. A suite of models was developed to test these hypotheses. Data included 32 years of recruitment and spawning biomass estimates derived from a stock assessment model and wind and temperature indices customized to the environmental exposure of age‐0 northern rock sole in the eastern Bering Sea. The predictive ability of the models was evaluated, and the models were used to forecast recruitment to age‐4 for recent year classes which are poorly retained by the standard multi‐species bottom trawl survey gear. Models which included wind and temperature indices performed better than a naïve forecast based on the running mean. The best‐performing model was a categorical model with wind and temperature thresholds, which explained 49% of the variation in recruitment. Ricker models performed more poorly than models without a spawning biomass term, providing no evidence that recruitment is related to stock size. The models forecast higher recruitment for the most recent year classes (2015–2018) than for prior year classes with observed poor recruitment (2006–2013). These environment‐based recruitment forecasts may improve recruitment estimates for the most recent year classes and facilitate study of the effects of future climate change on northern rock sole population dynamics.

Prospective Environmental Analyses of Emerging Technology: A Critique, a Proposed Methodology, and a Case Study on Incremental Sheet Forming - Daniel R. Cooper; Timothy G. Gutowski (Journal of Industrial Ecology, 2020)
Summary Prospective environmental assessment of emerging technology is necessary in order to inform designers of beneficial changes early in a technology's development, and policy makers looking to fund projects and nudge manufacturers toward the most sustainable application of a technology. Existing analyses often have shortcomings such as failing to consider the environmental impacts in all stages of a product's life cycle; implicitly assuming that the emerging technology will be cost‐effective wherever it is technically viable; and assuming optimistic application scenarios that discontinue long‐established trends in human behavior. In this article, we propose a new approach, complementary to the prospective and anticipatory life cycle assessment literature, addressing the above concerns and attempting to make sense of the large uncertainties inherent in such analyses by using distributions to model all the inputs. The paper focuses on emerging manufacturing technologies, such as incremental sheet forming (ISF), but the issues examined are also applicable to new end‐use products, such as autonomous vehicles. This paper makes use of approaches (such as Bass modeling and product cannibalization considerations) familiar to those in the business community who anticipate market diffusion of a new technology and the effect on existing technology sales. The proposed methodology is demonstrated by estimating the potential environmental impacts in the U.S. car industry by 2030 of an emerging double‐sided ISF process. Energy and cost models of ISF and drawing are used to estimate potential mean savings of around 100 TJ primary and 60 million U.S. dollars per year by 2030.

Late Quaternary sea‐level change and evolution of Belfast Lough, Northern Ireland: new offshore evidence and implications for sea‐level reconstruction - Ruth M. K. Plets; S. Louise Callard; J. Andrew G. Cooper; Joseph T. Kelley; Daniel F. Belknap; Robin J. Edwards; Antony J. Long; Rory J. Quinn; Derek W. T. Jackson (Journal of Quaternary Science, 2019)
The interplay of eustatic and isostatic factors causes complex relative sea‐level (RSL) histories, particularly in paraglacial settings. In this context the past record of RSL is important in understanding ice‐sheet history, earth rheology and resulting glacio‐isostatic adjustment. Field data to develop sea‐level reconstructions are often limited to shallow depths and uncertainty exists as to the veracity of modelled sea‐level curves. We use seismic stratigraphy, 39 vibrocores and 26 radiocarbon dates to investigate the deglacial history of Belfast Lough, Northern Ireland, and reconstruct past RSL. A typical sequence of till, glacimarine and Holocene sediments is preserved. Two sea‐level lowstands (both max. −40 m) are recorded at c. 13.5 and 11.5k cal a bp . Each is followed by a rapid transgression and subsequent periods of RSL stability. The first transgression coincides temporally with a late stage of Meltwater Pulse 1a and the RSL stability occurred between c. 13.0 and c. 12.2k cal a bp (Younger Dryas). The second still/slowstand occurred between c. 10.3 and c. 11.5k cal a bp . Our data provide constraints on the direction and timing of RSL change during deglaciation. Application of the Depth of Closure concept adds an error term to sea‐level reconstructions based on seismic stratigraphic reconstructions.

Overexpressing ovotransferrin and avian β-defensin-3 improves antimicrobial capacity of chickens and poultry products - Caitlin A. Cooper; Mark L. Tizard; Tamsyn Stanborough; Sean C. Moore; P. Scott Chandry; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Daniel S. Layton; Kirsten R. Morris; Robert J. Moore; Narelle Fegan; et al. (Transgenic Research, 2019)

Contractile protein biochemistry in the Pollard Lab in Baltimore - Daniel P. Kiehart; John A. Cooper (Biophysical Reviews, 2018)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Optimising physiochemical control of invasive Japanese knotweed - Daniel Jones; Gareth Bruce; Mike S. Fowler; Rhyan Law-Cooper; Ian Graham; Alan Abel; F. Alayne Street-Perrott; Daniel Eastwood (Biological Invasions, 2018)
Japanese knotweed, Fallopia japonica var. japonica , causes significant disruption to natural and managed habitats, and provides a model for the control of invasive rhizome-forming species. The socioeconomic impacts of the management of, or failure to manage, Japanese knotweed are enormous, annually costing hundreds of millions of pounds sterling (GBP£) in the UK alone. Our study describes the most extensive field-based assessment of F. japonica control treatments undertaken, testing the largest number of physical and/or chemical control treatments (19 in total) in replicated 225 m 2 plots over 3 years. Treatments focused on phenology, resource allocation and rhizome source–sink relationships to reduce the ecological impacts of controlling F. japonica . While no treatment completely eradicated F. japonica, a multiple-stage glyphosate-based treatment approach provided greatest control. Increasing herbicide dose did not improve knotweed control, but treatments that maximised glyphosate coverage, e.g., spraying versus stem injection, and exploited phenological changes in rhizome source–sink relationships caused the greatest reduction of basal cover and stem density after 3 years. When designing management strategies, effective control of F. japonica may be achieved by biannual (summer and autumn) foliar glyphosate applications at 2.16 kg AE ha −1 , or by annual application of glyphosate in autumn using stem injection at 65.00 kg AE ha −1 or foliar spray at 3.60 kg AE ha −1 . Addition of other herbicides or physical treatment methods does not improve control. This work demonstrates that considering phenology, resource allocation and rhizome source–sink relationships is critical for the control of invasive, rhizome forming species.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Inter- and intra-species intercropping of barley cultivars and legume species, as affected by soil phosphorus availability - Tegan Darch; Courtney D. Giles; Martin S. A. Blackwell; Timothy S. George; Lawrie K. Brown; Daniel Menezes-Blackburn; Charles A. Shand; Marc I. Stutter; David G. Lumsdon; Malika M. Mezeli; Renate Wendler; Hao Zhang; et al. (Plant and Soil, 2018)

Opportunities for mobilizing recalcitrant phosphorus from agricultural soils: a review - Daniel Menezes-Blackburn; Courtney Giles; Tegan Darch; Timothy S. George; Martin Blackwell; Marc Stutter; Charles Shand; David Lumsdon; Patricia Cooper; Renate Wendler; Lawrie Brown; Danilo S. Almeida; et al. (Plant and Soil, 2018)

Predicting habitat suitability for eleven imperiled fluvial freshwater mussels - Wesley M. Daniel; Arthur R. Cooper; Peter J. Badra; Dana M. Infante (Hydrobiologia, 2018)

Note on the Rate and Energy Efficiency Limits for Additive Manufacturing - Timothy Gutowski; Sheng Jiang; Daniel Cooper; Gero Corman; Michael Hausmann; Jan‐Anders Manson; Timo Schudeleit; Konrad Wegener; Matias Sabelle; Jorge Ramos‐Grez; Dusan P. Sekulic (Journal of Industrial Ecology, 2017)
Summary We review the process rates and energy intensities of various additive processing technologies and focus on recent progress in improving these metrics for laser powder bed fusion processing of metals, and filament and pellet extrusion processing of polymers and composites. Over the last decade, observed progress in raw build rates has been quite substantial, with laser metal processes improving by about 1 order of magnitude, and polymer extrusion processes by more than 2 orders of magnitude. We develop simple heat transfer models that explain these improvements, point to other possible strategies for improvement, and highlight rate limits. We observe a pattern in laser metal technologies that mimics the development of machine tools; an efficiency plateau, where faster rates require more power with no change in energy nor rate efficiency.

Distribution of serum levels of persistent organic pollutants, heterocyclic aromatic amine theoretical intake and nutritional cofactors in a semi-rural island population - Daniel Carrizo; Sarah F. Brennan; Olivier P. Chevallier; Jayne Woodside; Kevin M. Cooper; Marie M. Cantwell; Geraldine Cuskelly; Christopher T. Elliott (Environmental Science and Pollution Research, 2017)

Improving estimates of population status and trend with superensemble models - Sean C Anderson; Andrew B Cooper; Olaf P Jensen; Cóilín Minto; James T Thorson; Jessica C Walsh; Jamie Afflerbach; Mark Dickey‐Collas; Kristin M Kleisner; Catherine Longo; Giacomo Chato Osio; Daniel Ovando; et al. (Fish and Fisheries, 2017)
Fishery managers must often reconcile conflicting estimates of population status and trend. Superensemble models, commonly used in climate and weather forecasting, may provide an effective solution. This approach uses predictions from multiple models as covariates in an additional “superensemble” model fitted to known data. We evaluated the potential for ensemble averages and superensemble models (ensemble methods) to improve estimates of population status and trend for fisheries. We fit four widely applicable data‐limited models that estimate stock biomass relative to equilibrium biomass at maximum sustainable yield (B/ B MSY ). We combined these estimates of recent fishery status and trends in B/ B MSY with four ensemble methods: an ensemble average and three superensembles (a linear model, a random forest and a boosted regression tree). We trained our superensembles on 5,760 simulated stocks and tested them with cross‐validation and against a global database of 249 stock assessments. Ensemble methods substantially improved estimates of population status and trend. Random forest and boosted regression trees performed the best at estimating population status: inaccuracy (median absolute proportional error) decreased from 0.42 – 0.56 to 0.32 – 0.33, rank‐order correlation between predicted and true status improved from 0.02 – 0.32 to 0.44 – 0.48 and bias (median proportional error) declined from −0.22 – 0.31 to −0.12 – 0.03. We found similar improvements when predicting trend and when applying the simulation‐trained superensembles to catch data for global fish stocks. Superensembles can optimally leverage multiple model predictions; however, they must be tested, formed from a diverse set of accurate models and built on a data set representative of the populations to which they are applied.

Does the combination of citrate and phytase exudation in Nicotiana tabacum promote the acquisition of endogenous soil organic phosphorus? - Courtney D. Giles; Timothy S. George; Lawrie K. Brown; Malika M. Mezeli; Alan E. Richardson; Charles A. Shand; Renate Wendler; Tegan Darch; Daniel Menezes-Blackburn; Patricia Cooper; Marc I. Stutter; David G. Lumsdon; et al. (Plant and Soil, 2017)

The Environmental Impacts of Reuse: A Review - Daniel R. Cooper; Timothy G. Gutowski (Journal of Industrial Ecology, 2017)
Summary The fear that human consumption is causing climate change, biodiversity loss, and mineral scarcity has recently prompted interest in reuse because of the intuitive belief that it reduces new production and waste. The environmental impacts of reuse have, however, received little attention—the benefits typically assumed rather than understood—and consequently the overall effects remain unclear. In this article, we structure the current work on the topic, reviewing the potential benefits and pitfalls described in the literature and providing a framework for future research. Many products’ use‐phase energy requirements are decreasing. The relative importance of the embodied impacts from initial production is therefore growing and the prominence of reuse as an abatement strategy is likely to increase in the future. Many examples are found in the literature of beneficial reuse of standardized, unpowered products and components, and repairing an item is always found to be less energy intensive than new production. However, reusing a product does not guarantee an environmental benefit. Attention must be paid to restoring and upgrading old product efficiencies, minimizing overspecification in the new application, and considering whether more efficient, new products exist that would be more suitable. Cheap, reused goods can allow many consumers access to products they would otherwise have been unable to afford. Though socially valuable, these sales, which may help minimize landfill in the short term, can represent additional consumption rather than a net environmental benefit compared to the status quo.

Particulate accumulations in the vital organs of wild Brevoortia patronus from the northern Gulf of Mexico after the Deepwater Horizon oil spill - Daniel R. Millemann; Ralph J. Portier; Gregory Olson; Carolyn S. Bentivegna; Keith R. Cooper (Ecotoxicology, 2015)

Associations of prostate cancer risk variants with disease aggressiveness: results of the NCI-SPORE Genetics Working Group analysis of 18,343 cases - Brian T. Helfand; Kimberly A. Roehl; Phillip R. Cooper; Barry B. McGuire; Liesel M. Fitzgerald; Geraldine Cancel-Tassin; Jean-Nicolas Cornu; Scott Bauer; Erin L. Van Blarigan; Xin Chen; David Duggan; Elaine A. Ostrander; et al. (Human Genetics, 2015)

Effects of enamel matrix genes on dental caries are moderated by fluoride exposures - John R. Shaffer; Jenna C. Carlson; Brooklyn O. C. Stanley; Eleanor Feingold; Margaret Cooper; Michael M. Vanyukov; Brion S. Maher; Rebecca L. Slayton; Marcia C. Willing; Steven E. Reis; Daniel W. McNeil; Richard J. Crout; et al. (Human Genetics, 2015)

Palate Variation and Evolution in New World Leaf-Nosed and Old World Fruit Bats (Order Chiroptera) - Daniel W. Sorensen; Claire Butkus; Lisa Noelle Cooper; Chris J. Cretekos; John J. Rasweiler; Karen E. Sears (Evolutionary Biology, 2014)

Assessing and managing data‐limited ornamental fisheries in coral reefs - Rod Fujita; Daniel J Thornhill; Kendra Karr; Cara H Cooper; Laura E Dee (Fish and Fisheries, 2014)
Coral reefs support numerous ornamental fisheries, but there are concerns about stock sustainability due to the volume of animals caught. Such impacts are difficult to quantify and manage because fishery data are often lacking. Here, we suggest a framework that integrates several data‐poor assessment and management methods in order to provide management guidance for fisheries that differ widely in the kinds and amounts of data available. First, a resource manager could assess the status of the ecosystem (using quantitative metrics where data are available and semi‐quantitative risk assessment where they are not) and determine whether overall fishing mortality should be reduced. Next, productivity susceptibility analysis can be used to estimate vulnerability to fishing using basic information on life history and the nature of the fishery. Information on the relative degree of exploitation (e.g. export data or ratios of fish density inside and outside no‐take marine reserves) is then combined with the vulnerability ranks to prioritize species for precautionary management and further analysis. For example, species that are both highly exploited and vulnerable are good candidates for precautionary reductions in allowable capture. Species that appear to be less vulnerable could be managed on a stock‐specific basis to prevent over‐exploitation of some species resulting from the use of aggregate catch limits. The framework could be applied to coral reef ornamental fisheries which typically lack landings, catch‐per‐unit‐effort and age‐size data to generate management guidance to reduce overfishing risk. We illustrate the application of this framework to an ornamental fishery in Indonesia.

A Hollywood drama of butterfly extirpation and persistence over a century of urbanization - Timothy C. Bonebrake; Daniel S. Cooper (Journal of Insect Conservation, 2014)

Bottom‐up biodiversity effects increase resource subsidy flux between ecosystems - Daniel C. Allen; Caryn C. Vaughn; Jeffrey F. Kelly; Joshua T. Cooper; Michael H. Engel (Ecology, 2012)
Although biodiversity can increase ecosystem productivity and adjacent ecosystems are often linked by resource flows between them, the relationship between biodiversity and resource subsidies is not well understood. Here we test the influence of biodiversity on resource subsidy flux by manipulating freshwater mussel species richness and documenting the effects on a trophic cascade from aquatic to terrestrial ecosystems. In a mesocosm experiment, mussel effects on algae were linked through stable isotope analyses to mussel‐derived nitrogen subsidies, but mussel biodiversity effects on algal accumulation were not significant. In contrast, mussel biodiversity significantly increased aquatic insect emergence rates, because aquatic insects were responding to mussel‐induced changes in algal community structure instead of algal accumulation. In turn, mussel biodiversity also significantly increased terrestrial spider abundance as spiders tracked increases in aquatic insect prey after a reproduction event. In a comparative field study, we found that sites with greater mussel species richness had higher aquatic insect emergence rates. These results show that, because food webs in adjacent ecosystems are often linked, biodiversity effects in one ecosystem can influence adjacent ecosystems as well.

ERP correlates of response inhibition after-effects in the stop signal task - Daniel J. Upton; Peter G. Enticott; Rodney J. Croft; Nicholas R. Cooper; Paul B. Fitzgerald (Experimental Brain Research, 2010)

Comparison of the Cardiac Electrophysiology and General Toxicology of Two Formulations of Intravenous Amiodarone in Dogs - Daniel J. Cushing; Warren D. Cooper; Michael R. Gralinski; Raymond J. Lipicky; Peter J. Kudenchuk; Peter R. Kowey (Cardiovascular Toxicology, 2009)

Effects of ontogeny, temperature, and light on vertical movements of larval Pacific cod ( Gadus macrocephalus ) - THOMAS P. HURST; DANIEL W. COOPER; JOEL S. SCHEINGROSS; ERIN M. SEALE; BENJAMIN J. LAUREL; MARA L. SPENCER (Fisheries Oceanography, 2009)
The role of behavior, especially vertical migration, is recognized as a critical component of realistic models of larval fish dispersion. Unfortunately, our understanding of these behaviors lags well behind our ability to construct three‐dimensional flow‐field models. Previous field studies of vertical behavior of larval Pacific cod ( Gadus macrocephalus ) were limited to small, preflexion stages (≤11 mm SL) in a narrow range of thermal conditions. To develop a more complete picture of larval behavior, we examined the effects of ontogeny, temperature, and light on vertical responses of larval Pacific cod in experimental columns. While eggs were strictly demersal, yolk‐sac larvae displayed a strong surface orientation as early as 1 day post hatch (∼ 5 mm SL). Consistent with field observations, small preflexion larvae ( 15 mm SL) in experimental columns was consistent with a diel vertical migration and independent of water temperature: fish were more widely distributed in the column, and median positions were consistently deeper at higher light levels. These laboratory observations are combined with observations from discrete‐depth (MOCNESS) sampling in the Gulf of Alaska to characterize the vertical distribution of larval Pacific cod and contrast ontogenetic patterns with walleye pollock ( Theragra chalcogramma ). The vertical movements of larval Pacific cod described here will be applied in the development of dispersal projections from Gulf of Alaska spawning grounds.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

CAN WE IMPROVE ESTIMATES OF JUVENILE DISPERSAL DISTANCE AND SURVIVAL - Caren B. Cooper; Susan J. Daniels; Jeffrey R. Walters (Ecology, 2008)
Estimates of distributions of natal dispersal distances and juvenile recruitment rates in open populations are strongly influenced by the extent and shape of the areas sampled. Techniques to improve biased dispersal and survival estimates include area–ratio methods based on weighting observations by sampling effort, the extent and shape of the area sampled, and the amount and distribution of preferred habitat surrounding the area sampled. We partitioned territories within the boundaries of a large, almost geographically closed, population of individually marked Red‐cockaded Woodpeckers ( Picoides borealis ) and estimated dispersal and survival parameters from hypothetical smaller study areas (sampling areas) of varying sizes and shapes in order to examine whether an area–ratio method provides accurate or improved estimates of juvenile dispersal distance and survival. Non‐aggregated sampling areas resulted in the detection of fewer dispersal events, but because of their large spatial extent, produced unbiased dispersal estimates. The use of aggregated sampling areas (circular or linear) resulted in the detection of higher numbers of dispersal events, but produced biased dispersal estimates that were generally improved by the area–ratio method. Area–ratio corrections usually provided better estimates of median dispersal distance than uncorrected estimates. Survival to breeding was usually underestimated and often not improved by the area–ratio method, regardless of extent and shape of the sampling area. Estimates of juvenile survival to breeding were improved by assuming that rates of emigration were equivalent to immigration, and correcting survival estimates accordingly. Small, local studies should use an area–ratio method to improve their estimates of median dispersal distance. Because the correction method estimates relative, but not absolute, numbers of individuals dispersing across distance categories, the area–ratio method should not be used for estimating survival. Non‐aggregated sampling areas may be an effective design to increase spatial extent (and thus decrease bias) without proportionately increasing the amount of habitat sampled.